A Comparative Study on the Position and Rights of Illegitimate Children in Malaysia and Indonesia - Ghapa, Norhasliza; Hamid, Noor Ashikin; Harun, Noraida; Windar, Rusmilawati; Rosli, Iyllyana Che (Faculty of Law, University of Muhammadiyah Malang, 2026)
This study is motivated by the pressing concern that illegitimate children often face legal and social disadvantages, especially in matters related to lineage (nasab), inheritance, and paternal affiliation. The core problem lies in reconciling classical Islamic jurisprudence with contemporary legal developments that seek to uphold children welfare and human dignity. This paper aims to conduct qualitative research by doctrinal approach and comparative analysis of the legal frameworks in Malaysia and Indonesia regarding the status and rights of illegitimate children. In Malaysia, the prevailing interpretation under the Syariah Court Enactments generally denies nasab and inheritance rights to such children, adhering to traditional fiqh doctrines. In contrast, Indonesia has adopted a more progressive stance, especially following the Constitutional Court’s landmark decision No. 46/PUU-VIII/2010, which allows children born out of wedlock to claim civil rights through biological linkage. Using a qualitative doctrinal and comparative legal methodology, the study evaluates how far these approaches align with the objectives of Islamic law (Maqasid al-Sharia), particularly in protecting the best interests of the children. The paper concludes by proposing harmonized legal reforms that uphold justice, child welfare, and the ethical principles of Islamic family law.